A comparative study of impact of breastfeeding practices on the nutritional status of the infants among the working and non-working women - A., Ashok; H., Shwetha J.; K., Mahesh T. (International Journal of Contemporary Pediatrics, 2018)
Background: Amongst the many determinants that influence the exclusivity of breastfeeding, the working status of the mother is the probably the most important. Methods: A comparative analysis was done regarding the feeding pattern in early infancy between working and non-working mothers. The anthropometric indices of the groups were studied and compared. 50 working mothers and non-working mothers were taken up for the study and they were followed on regular intervals i.e., 6, 10, 14, 18 and 24 weeks. Results: Age of working mothers was more than non-working mothers. 51.06% mothers in study group and 85.41% mothers in control group had exclusively breastfed their infants’ upto 18 weeks. The mean weight was 7.77 (0.52) and 7.35 (0.59) among female study and control group, 8.19 (0.50) and 7.84 (0.50) among male study and control group. Conclusions: Breastfeeding practices were comparable among the study and control group till the study group availed their maternity leave. Anthropometry is comparable among the study and control group for female babies, but there is a significant difference in anthropometry measures among male babies.